PERAN SEKTOR PERTANIAN TERHADAP PEREKONOMIAN KABUPATEN CILACAP PERIODE 2002-2013 (Dengan Pendekatan Tipologi Klassen, Shift Share, dan Loqation Quetient) - Ilham Alkaf; Siti Rochaeni; Achmad Tjachja Nugraha (AGRIBUSINESS JOURNAL, 2017)
The purpose of this study are: 1) to analyze the position of each sub-sector of agriculture in Cilacap economies, 2) to analyze the growth of each sub-sector of agriculture in Cilacap economies, and 3) to analyze which sub-sectors become the agricultural subsector basis in Cilacap. The Klassen Typology, the Shift Share, and the Loqation Quetient were employed to analyze the data of GDRP Cilacap and Central Java province from 2002 until 2013. The analysis showed that the position of sub-sectors of agriculture in Cilacap economies from 2002 until 2013 are: 1) sub-sector of food crops, livestocks, fisheries and forestries is in the lagging position, and 2) sub-sector of plantations is in the potential position. Based on the proportional growth component, plantations and livestocks experienced rapid growths. Subsequent analyses indicate that food crops and forestries become the basis of Cilacap economies.